Simulation of the dry matter production and seed yield of common beans under varying soil water and salinity conditions - Adiku, S.G.K.; Renger, M.; Wessolek, G.; Facklam, M.; Hecht-Bucholtz, C. (Agricultural Water Management, 2001)
We present a model that simulates the effects of water and salinity stress on the growth of beans. The model derives a combined soil water/salinity stress factor from the total water potential (combination of the matric and the osmotic potentials) and uses this stress factor as a growth limiter in a growth model. The model was tested on data obtained from two greenhouse trials of beans (Phaseolus vulgaris) grown under a range of soil water and salinity conditions. The simulated dry weight of the bean generally followed those observed. In the first trial, the comparison between simulated and observed total dry weight and seed yield gave R2 values of 0.97 and 0.92, respectively. Comparison of the simulated to the observed dry weight for the second trial gave R2 values of 0.85 and 0.89, respectively. These indicate a good performance of the model in general. The principle of deriving a combined water/salinity stress from the matric and osmotic potentials is simple and can be included as a simple routine in many existing crop models without much difficulty. © 2001 Elsevier Science B.V.
Keywords: Beans; Crop growth simulation; Soil salinity; Soil water stress